Design of a light and fast energy degrader for a compact superconducting gantry with large momentum acceptance. (May 2020) - Liu, Xu; Wang, Wei; Liang, Zhikai; Zhao, Runxiao; Liu, Kaifeng; Qin, Bin
Highlights: Whole energies are grouped into three ranges, and continuous energy degradation. Light and compact moving parts can help achieve fast energy switching. The energy layers can be increased in case of protons with large energy spread. Great improvement of 40%–60% on beam transmission efficiency in the lower energies. Abstract: Purpose: Proton therapy is a precise radiation cancer treatment with low side effects. To reduce the cost and footprint of the facility, the superconducting gantry with large momentum acceptance becomes a potential solution. Benefit from this feature, beam delivery time depends largely on the energy-switching process and short time is helpful for increasing the number of volume repaintings. Methods: This note introduces an energy degrader with lightweight moving parts and a new hybrid structure (wedge-block-block). The total energies are separated into three stages and are degraded at fixed rates in two boron carbide blocks. As only one pair of graphite wedges is used for energy modulation, the energy switching at each step reaches a 10 ms level. Results: The transport process in the degrader was simulated in TOPAS. After the degradation, the maximum energy spread ( 1 σ ) was approximately 5.5 %, and the distance between successive energy layers can be increased for treating non-sensitive tissues. Six configurations of the hybrid degrader achieved distinctly higher transmission efficiencies than the usual graphite multi-wedge degrader. Finally, the configuration that maximized the beam transmission in the lower-energy range (namely, the W– B 1 – B 2 configuration) was chosen as the degrader. Conclusions: This new degrader not only improved the transmission efficiency, but also reduced the energy-switching time by virtue of its light and compact structure.